Effect of desensitizing agents on dentin hypersensitivity after non-surgical periodontal therapy: A systematic review and meta-analysis - de Oliveira, Roberta Pimentel; Alencar, Cristiane de Melo [UNESP]; Silva, Fábio Alves; Magno, Marcela Baraúna; Maia, Lucianne Cople; Silva, Cecy Martins (Elsevier, 2020)
Objective: To investigate the effectiveness of desensitizing agents (DA) on dentin hypersensitivity (DH) after non-surgical periodontal treatment (NSPT) through a systematic review and meta-analysis. Data: The PICO strategy was used to include randomized clinical trials in human subjects with DH (P) after NSPT treated with DA (I) compared to those treated with placebo or control (C) to identify DH relief (O). The Cochrane guidelines and GRADE was used to classify the risk of bias and the quality of the evidence, respectively. Sources: PubMed, Web of Science, Scopus, Lilacs, Cochrane Library databases, and OpenGrey were searched on the 20th of May 2020. Study selection: Nine studies were included in the quantitative synthesis. Five meta-analyses were performed. Three meta-analyzes assessed the effectiveness of DA compared to a placebo or control in relation to pain assessment stimuli and two meta-analyzes assessed the mechanism of action of DA. For the mechanical stimulus in overall analysis, the control group presented a higher mean of pain reduction (SMD 1.03 [0.73, 1.32], p < 0.001) with very low certainty of evidence. For water (SMD -0.78 [-1.22, -0.35], p = 0.0009) and evaporative in overall analysis (SMD -1.21 [-1.79, -0.64], p < 0.001) stimuli, the DA decreased DH pain with very low and low certainty of evidence, respectively. Conclusion: Due to the limited quality of evidence, there is no definitive conclusion on the effectiveness of DA on DH after NSPT. Thus, further clinical studies with a low risk of bias and high-quality evidence are encouraged to reinforce the certainty of evidence on that issue. Clinical significance: The use of desensitizing agents show promise for relief of dentin hypersensitivity after non-surgical periodontal therapy.
Keywords: Clinical trial; Dentin hypersensitivity; Desensitizing agents; Non-surgical periodontal treatment